Dynamics of reactant interfaces in irreversible reaction systems - Albano, Ezequiel Vicente (2000)
Recent progress in the study and understanding of the properties of interfaces between reactants in irreversible reaction systems, gained from Monte Carlo simulations, is reviewed and discussed. The displacement of unstable phases by stable ones causes the formation of interfaces. This mechanism is particularly relevant close to first-order irreversible phase transitions, where phase coexistence is observed. Different variants of the monomer-momomer and the monomer-dimer models exhibit such transitions, and they are therefore suitable for the study of interfacial properties. More specifically, due to stimulating experimental findings, the monomer-dimer model, which mimics the catalytic oxidation of carbon monoxide, has been the subject of extensive studies, which are discussed in detail.